Importance of Software Testing in Software Development - Kumar, Neeraj; Singla, Ayush (IJRDO -Journal of Computer Science Engineering, 2015)
Software development life cycle is a structure imposed on the development of a software product. Software development life cycle is closely linked to what has come to known as structured analysis and design. Testing is an important part of software development. Testing should be started as early as possible to make it a part of a process of deciding requirement .The major role of testing involves checking, that there should be no discrepancy in the software development process anywhere throughout. In my paper I have explained various phases and importance of testing in software development life-cycle. Keywords: Software Development Life Cycle, Software Development Process, Software Testing